Vulnerabilidade/fragilidade ambiental à erosão no município de Nossa Senhora da Glória/SE - Bastos Júnior, Edson Magalhães (2016)
The city of Nossa Senhora da Glória – Sergipe, Brazil - is located in the northeastern semiarid region, and presents a geological-geomorphological context marked by its insertion into the backlands pediplain, whose pediplained surfaces developed on a variable lithology, predominantly as a member of the Macururé Domain in Sergipe's Fold Range. These surfaces, of which part are arranged in tabular interfluves system with high dissection developed during the Quaternary, are currently occupied predominantly by farming, in greater proportion, with large tracts of cultivated and pastured areas surrounding some niches of arboreal and shrub forest remnants. These are interconnected by a multivariate herbaceous cover and two networks: a natural river drainage, and other terrestrial circulation (several entries). This has some significant evidence of erosion located in the form of individual gullies, geomorphological facts that suggested a morphodynamic anthropogenic inclination. For this reason, the research was based on the use of geotechnology, to map vulnerability and environmental vulnerability to erosion across surface extension of the municipality. The theoretical and methodological framework set out the joint of two reference models in Geosciences culminating in the drafting of a synthesis map. The methodological development stages were grouped into four general and progressive levels of achievement, and followed the interpretation of Digital Elevation Models and multispectral optical satellite images, and data integration and derivation of lithology, soil conditions, climate, vegetation and use of land in Geographic Information Systems environment. The study shows that currently ecodynamic units in dynamic stability situation predominate, although the association between highly exposed litholic soils, highly dissected terrains in tabular interfluves and areas of concave-converging strands, intersected by roads, keep potential risk factor to future changes of that balance.